Photoacoustic detection of ozone with a red laser diode - Keeratirawee, Kanchalar; Hauser, Peter C. (Talanta (Oxford), 2021)
The photoacoustic detection of ozone using the Chappuis band is demonstrated. A visible red laser diode emitting at 638 nm was employed as a light source. The photoacoustic cell consisted of a conventional resonance tube with a MEMS (microelectromechanical systems) microphone placed outside an opening along the tube. A calibration curve for the range from 33 ppmV to 215 ppmV was found to be highly linear with a coefficient of determination (r2) of 0.9999, when allowing for different measurement frequencies to account for shifts in the speed of sound due to changes in the gas matrix. The limit of detection was found to be 1.6 ppmV for an optical power of the laser diode of about 130 mW. [Display omitted] •A visible laser diode is employed for the first time.•The light source is inexpensive.•The detection limit is in the low ppmV range.